Program ADEM sebagai Sarana Integrasi Sosial dan Kebhinekaan di Sekolah Menengah Atas - Arini Puspa Wardani; Alifa Izzatun Nisa; Kenny Syalwatyarsa; Rifana Nurul Nisya; Sahila Putri Airin; Syahbila Zalfa; Wulan Asmi Nurapipah; Bunyamin Maftuh; Supriyono Supriyono (Dimensia: Jurnal Kajian Sosiologi, 2024)
This study aims to analyze the extent of the application of multiculturalism in SMAN 1 Ngamprah through the Secondary Education Affirmation (ADEM) program as an effort to create harmony and tolerance between students from different cultures, religions, and ethnicities. The research method is used through a qualitative approach. Data were collected through observation and in-depth interviews with teachers and students at SMAN 1 Ngamprah. The results of the study show that the implementation of Multiculturalism education at SMAN 1 Ngamprah is through the ADEM Program. The results of the study show that the implementation of the ADEM program has been carried out quite well. There are challenges of cultural adaptation for students from the ADEM program, namely difficulties in adapting to the environment such as language, customs, values, and social norms. With the holding of the ADEM program, a school environment is created that upholds tolerance, respect, and mutual respect for differences between students so that students from the ADEM program and regular students.